2018
DOI: 10.1037/tra0000339
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological investigation of attentional bias in a PTSD population.

Abstract: The present study provided no support for facilitated engagement in this sample of patients. Possible interpretations of the results related to differential processing of target probes replacing angry-neutral face pairs are discussed. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Finally, PTSD+ display greater P2 amplitude to angry faces than PTSD− post- as opposed to pre-deployment (65). With respect to P3 differences, PTSD+ display longer frontocentral P3 latency to happy faces than PTSD− with history of trauma (99) as well as larger P3 amplitude to neutral than angry faces during a dot probe task (71). During later elaborative processing, PTSD symptoms in combat veterans are linked to smaller LPP amplitude to angry faces (66, 78, 79).…”
Section: Event Related Potential Markers Of Trauma Experience and Posmentioning
confidence: 99%
“…Finally, PTSD+ display greater P2 amplitude to angry faces than PTSD− post- as opposed to pre-deployment (65). With respect to P3 differences, PTSD+ display longer frontocentral P3 latency to happy faces than PTSD− with history of trauma (99) as well as larger P3 amplitude to neutral than angry faces during a dot probe task (71). During later elaborative processing, PTSD symptoms in combat veterans are linked to smaller LPP amplitude to angry faces (66, 78, 79).…”
Section: Event Related Potential Markers Of Trauma Experience and Posmentioning
confidence: 99%
“…On a neurophysiological level, we found diverging result patterns for PTSD and anxiety: A greater P1 in the friend than in the stranger condition predicted greater PTSD symptoms, whereas a greater P1 and N1 in the stranger than in the friend condition was correlated with greater anxiety. Although diverging, both of these patterns have been found in traumatized samples: Shah et al ( 2018 ) found a reduced P1 for non-threatening as opposed to threatening stimuli in PTSD patients, whereas others (Fang et al, 2019 ; Zhang et al, 2014 ) have found a greater P1 and N1 for threatening as opposed to non-threatening stimuli in traumatized individuals. Based on these findings, one could speculate that attentional avoidance in the presence of an approaching stranger – representing potential threat – might predispose traumatized individuals towards PTSD development, whereas hypervigilant attention towards an approaching strangers – representing potential threat – could be a precursor to the development of anxiety after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, two studies (Fang et al, 2019 ; Zhang, Kong, Han, Ul Hasan, & Chen, 2014 ) found an opposing pattern, indicating hypervigilant attention (greater P1 and N1) for threatening as opposed to non-threatening stimuli in traumatized individuals (for a more detailed account on attentional processing in PTSD see e.g. Shah et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations